Quantum dynamics study of fulvene double bond photoisomerization: the role of intramolecular vibrational energy redistribution and excitation energy - Blancafort, Lluís; Gatti, Fabien; Meyer, Hans-Dieter (The journal of chemical physics, 2011)
The double bond photoisomerization of fulvene has been studied with quantum dynamics calculations using the multi-configuration time-dependent Hartree method. Fulvene is a test case to develop optical control strategies based on the knowledge of the excited state decay mechanism. The decay takes place on a time scale of several hundred femtoseconds, and the potential energy surface is centered around a conical intersection seam between the ground and excited state. The competition between unreactive decay and photoisomerization depends on the region of the seam accessed during the decay. The dynamics are carried out on a four-dimensional model surface, parametrized from complete active space self-consistent field calculations, that captures the main features of the seam (energy and locus of the seam and associated branching space vectors). Wave packet propagations initiated by single laser pulses of 5-25 fs duration and 1.85-4 eV excitation energy show the principal characteristics of the first 150 fs of the photodynamics. Initially, the excitation energy is transferred to a bond stretching mode that leads the wave packet to the seam, inducing the regeneration of the reactant. The photoisomerization starts after the vibrational energy has flowed from the bond stretching to the torsional mode. In our propagations, intramolecular energy redistribution (IVR) is accelerated for higher excess energies along the bond stretch mode. Thus, the competition between unreactive decay and isomerization depends on the rate of IVR between the bond stretch and torsion coordinates, which in turn depends on the excitation energy. These results set the ground for the development of future optical control strategies.
Gesehen am 30.03.2022